Licorice: desenvolvimento visual de personagens e cenários - Cappellotto, Anna Laura Cerioni [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Licorice is a concept art and illustration project with the objective of presenting the visual development of characters and scenarios. All the illustrated studies made for this project are showcased in artbook format.

Licorice é um projeto de ilustrações e concept art que tem como objetivo apresentar o desenvolvimento visual de personagens e cenários. Todos os estudos realizados para esse projeto foram reunidos em um artbook.
Licorice: visual development of characters and settings
Keywords: Design; Concept art; Artbook; Illustration; Personagens; Ilustração